Diglossie et standardisation dans l'Angleterre du xie au xve siècle. Regard croisé avec la Bretagne - Gary Manchec German (La Bretagne Linguistique)
The Norman Conquest of England (1066) profoundly and permanently altered not only the social order of England but also the English language. A diglossic relationship resulted, with Anglo-Norman French becoming the language of the ruling classes, while Latin continued as the language of the clergy. Until the beginning of the 14th century, English was considered the speech of merchant class and the peasantry.As early as the 10th century, but in a radically different sociohistorical and geopolitical framework, the Breton nobility gradually adopted French. In both cases, Breton and English adopted massive numbers of new words from French and Latin, often the same ones. This source remains a largely unexploited comparative tool for lexicographers of the three languages. In the case of English, native speakers still viscerally feel this Latinate vocabulary to be more sophisticated and intellectually superior to that of English origin, a form of diglossia internal to English which has lasted for 956 years. A similar situation existed in Brittany throughout the Middle Breton period.In this article, I trace the way in which the English language, by the middle of the 14th century, progressively served as a symbol of a new national identity that was at once religious, popular, and ethnic. It was also during this century that the Anglo-Norman nobility abandoned French, creating the conditions which contributed to the birth of a standard language from the 15th century onwards.